VD_FINDINFO HC / 2012 / 167 vom 8. Februar 2012 - VD Tribunal cantonal (2012)
MODÉRATION, HONORAIRES, AVOCAT, DÉCOMPTESENS GÉNÉRAL, RÉDUCTIONEN GÉNÉRAL | 12 let. i LLCA, 45 al. 1 LPAv, 48 LPAv, 50 al. 1 LPAv, 51 LPAv